Conteúdos relacionados ao enfrentamento da violência e violência infantil na formação de professores de educação física no Brasil - Silva, Sorlei Silva e (2024)
Child violence reaches alarming numbers and constitutes a social and global health problem. In this scenario, the importance of healthcare professionals being prepared to identify and address cases of violence, as well as implement preventive actions, is emphasized. Objective: To identify whether the themes of "violence" and "violence against children" are addressed in the curricula of undergraduate Physical Education courses in Brazil. Method: This is a documental research, of cross-sectional and descriptive nature, guided by the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) principles. Matrices and course syllabi of undergraduate Physical Education courses in Brazil were analyzed. Data analysis was performed through careful reading and examination of the collected materials, aiming to extract information and organize and interpret it according to the objectives of this research. Results: One hundred and eighty-two courses were included as a sample for this research. The majority of the courses are offered in the Northeast region of Brazil. Two courses, one on-site and one distance learning, offered by the same institution of higher education in the South region, addressed the theme of violence in the title of a curriculum discipline, namely, "Physical education and prevention of violence." Less than half of the courses covered the theme of violence in their syllabi, and only two specifically addressed child abuse. Forty-three syllabi included the theme of violence, with the majority being offered in courses located in the Northeast region and categorized as mandatory disciplines. Among these, only two specifically addressed violence against children. Conclusion: It is concluded that the theme of violence is not present in most of the syllabi of Physical Education courses. Specifically, in regards to violence against children, this content is rarely addressed in the syllabi. Thus, there are weaknesses in the approach to content related to the confrontation of child violence in the training of Physical Education teachers.